eCM 2010
DOI: 10.22203/ecm.v019a22
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of immortalized periodontal ligament progenitor cell line and its behavioural analysis on smooth and rough titanium surface

Abstract: Periodontal ligament (PDL) can be obtained from patients undergoing orthodontic treatment. PDL contains progenitor cells that can be expanded and differentiated towards several mesenchymal lineages in vitro. Furthermore, PDL-derived cells have been shown to generate bone-and PDL-like structures in vivo. Thus, PDL cells, combined with suitable biomaterials, represent a promising tool for periodontitisrelated research and PDL engineering.Here, a new PDL cell line using lentiviral gene transfer of human telomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…In the study two standard cell lines characterised before, namely PDL-(hTERT) cell line from Docheva et al (2010) and human AT-(hTERT) cell line derivative from Kohler et al (2013) were implemented. Both cell lines were cultured in DMEM/Ham′s F-12 (1:1 mixture) medium supplemented with stable glutamine (365.3 mg/L), 1 × MEM amino acids (all from Biochrom, Berlin, Germany), 10 % FBS and 1 % L-ascorbic acid-2-phosphate (both from SigmaAldrich, Steinheim, Germany) in a humidified incubator at constant 37 °C and 5 % CO 2 .…”
Section: Cell Preparation Prior Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study two standard cell lines characterised before, namely PDL-(hTERT) cell line from Docheva et al (2010) and human AT-(hTERT) cell line derivative from Kohler et al (2013) were implemented. Both cell lines were cultured in DMEM/Ham′s F-12 (1:1 mixture) medium supplemented with stable glutamine (365.3 mg/L), 1 × MEM amino acids (all from Biochrom, Berlin, Germany), 10 % FBS and 1 % L-ascorbic acid-2-phosphate (both from SigmaAldrich, Steinheim, Germany) in a humidified incubator at constant 37 °C and 5 % CO 2 .…”
Section: Cell Preparation Prior Implantationmentioning
confidence: 99%
“…Periodontal ligament (PDL)-derived cells are of particular importance as in comparison to tendon cells, in a way that they are much more easily accessible through the oral cavity and can be simply harvested especially from extracted teeth when patients have orthodontic treatments (Miura et al, 2003;Seo et al, 2004). Recently, several groups, including our, reported that PDL contains endogenous stem/progenitor cells (Bluteau et al, 2008;Docheva et al, 2010;Ivanovski et al, 2006), which express tendon-specific genes such as scleraxis and tenomodulin (Docheva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…24 It has been proven that the surface of metal implants plays a crucial role for the cell behavior and survival, the expression of specifc molecules and cell differentiation. 21 The complex reparative cells -biocompatible scaffolds is one the most attractive approaches for tissue regeneration. 25 …”
Section: Discussionmentioning
confidence: 99%
“…The procedures for cell culturing and storing were performed according to. 21 BioCompatiBility teSting Samples were placed in 8-well glass slides with a lid for cell cultures. 6 x 10 4 cells were added to each well and incubated for 96 hours.…”
Section: Pdl Cell Line Of Immortalized Precursor Cells From Periodontmentioning
confidence: 99%
“…The behavior of cellular population in contact with a metal depends directly on the microscopic properties of implants, such as topography, chemicals and surface energy [4,5]. While the effects of different types of surface treatments of titanium have been well-defined in osteoblastic cells and mesenchymal stem/stromal cells [13][14][15][16][17][18][19][20], studies focused on periodontal ligament (PDL) cells-titanium surface interactions are limited [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%